To Hedge or Not to Hedge: The Impact of the Global Financial Crisis on Corporate Hedging Strategy in FTSE 350 Companies - Thompson, Daniel (2010)
This work provides empirical evidence on corporate hedging strategy in relation to the recent global financial crisis using non survey data. This research will facilitate a greater understanding of how the financial crisis impacted hedging strategies in modern day risk management practice. Data on hedging activity was obtained via the FAME database and from the disclosures made in the financial statement footnotes of 205 non-financial firms subject to UK accounting standards. Based on the empirical evidence I draw the following conclusions: evidence uniformly supports the economies of scale theories; evidence is mixed with respect to the financial distress and underinvestment theories and evidence is inconsistent with the hedging substitute’s theory. In addition, evidence indicates an increase in hedging activity during the period of the financial crisis, specifically in regards to the mines, metals and minerals, and oil and gas industries, arguably due to events of the global financial crisis.